EVALUASI METODE PENAJAMAN CITRA MULTISPEKTRAL DENGAN MEMANFAATKAN KANAL PANKROMATIK - - Dianovita (Pusbindiklat - LIPI, 2010)
This paper studied three methods of pan-sharpenning of SPOT-4 image and evaluated the quality of the results. Three pan-sharpenning methods were applied to a scene of SPOT-4 image of K/J:287/364 acquiried on 25 July 2008 by using image processing software. Those three methods were IHS-RGB, Color Normalized (Brovey), and PCA (Principle Component Analysis). For IHS-RGB and Color Normalized (Brovey) methods the formulas written in Kartasasmita were used. These formula are practical to be used in image processing software and canbe understood theoritically. Similarly for PCA (Principle Component Analysis) method on this research the values of the elements of eigenvectors, which are required for doing the transformation and inversion, are calculated before then they are used in a new more practical equation and can be inputted to image processing software. It was expected that three mathematic equations from those three methods can be implemented easily in other image processing softwares and used for other multispectral image sharpenning by panchromatic band. An assessment to test the pan-sharpenning processes quantitatively and qualitatively were conducted. A qualitative assessment had been conducted by visual interpretation of pansharpened image. Quantitative assessments of pan-sharpened image was showed by change of spectral value range of each spectral channel, measureof the slope detail of pansharpened image from several object detail and the spectral information similarity between original and pansharpened images by Q Index and Correlation Coefficient. The results of this study are practical equations for PCA, IHS-RGB and Color Normalized (Brovey) Methods; pan-sharpened of SPOT-4 image; and quality assessment of pan-sharpened of SPOT-4 image.